The Influence of Picture Story Books on Elementary School Students' Reading Interest in the Jayapura Papua School Library - Komari; Emon Paranoan; Rosi F. Sumedi; Upi Laila Hanum; Herry W. Susanto; Merliana Trince (Journal of Education Reseach and Evaluation, 2024)
This research identifies the problem of low interest in reading among elementary school students, where only 30% of students in Indonesia have achieved an adequate level of reading ability. The urgency of this research lies in the urgent need to increase interest in reading to support students' literacy and critical thinking skills. The aim of the research is to describe the level of students' reading interest in picture story books and the role of the school library in providing appropriate reading materials. The research method used is a quantitative survey. The total research sample was 345 students from 10 elementary schools in Jayapura, Papua. Data collection techniques were used through distributing questionnaires and interviews to obtain more in-depth information. The research results showed that 80% of students had a high interest in reading picture books, 76% showed seriousness in reading and 74% were able to understand the content of the reading. These findings indicate that although interest in reading is high, access to picture story books still needs to be improved. This research concludes that school libraries play an important role in increasing students' interest in reading. The implication of this research is the need for reading literacy policies in schools and providing attractive book collections for students to build positive reading habits from an early age, in order to improve the overall quality of education.